Expo 2020 Dubai as Experiencescape to Build Image of Exhibiting Countries: Perspective of Polish Pavilion Personnel - GĘBAROWSKI, Marcin (Journal of Environmental Management and Tourism; Vol 16 No 3 (2025): JEMT, Volume XVI, Issue 3(79), Fall 2025, 2025)
The study aimed to explore world exhibitions (commonly referred to as Expos) as a place where image-related activities of exhibiting countries are performed – and the exploration was based on the experiencescape perspective. A reference was made to Expo, which in 2021 and 2022 was held in Dubai. An individual in-depth interview was employed (a semi-structured interview), which covered 20 people serving visitors in the Polish pavilion for three months during Expo 2020 Dubai. Empirical material was developed following the rules applicable to reflexive thematic analysis. The analysis of the empirical material made it possible to identify five topics (categories) characterising a contemporary Expo as experiencescape. The following topics were identified: (1) a unique presentation of almost all countries at one time and place; (2) multiple accompanying events; (3) promotion of countries through the latest means of expression; (4) a place with a unique atmosphere, where above-average experiences are delivered; (5) a space where event participants can be overstimulated. These categories should be the main areas of decision-making in the process of preparing and implementing national presentations, as well as provide directions for future scientific research dedicated to world exhibitions. The study shows originality, as no other work has been published in the scientific literature to date that has considered world exhibition grounds as experiencescape. Exhibiting countries were given guidelines to prepare national presentations meeting the expectations of Expo participants and ensuring the effectiveness of image-shaping activities.